Determinants of E-wallet Adoption Intention Using Extended Technology Acceptance Model: Evidence from Makassar City - Sri Wahyuni Nur; Ira Sahara; Andi Tenri Uleng Akal; Haikal Supardi; Irma Febrianti (Politeknik Ganesha Medan, 2026)
The rapid development of financial technology has accelerated the transition from cash-based to digital payment systems, particularly e-wallets. Although previous studies have widely examined e-wallet adoption, limited research has integrated behavioral adoption factors within the context of emerging digital financial ecosystems in developing urban areas such as Makassar City. This study aims to analyze the behavioral determinants influencing users’ intention to adopt e-wallets using an extended Technology Acceptance Model (TAM) incorporating trust as an additional construct. A quantitative approach was employed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 3.0. Data were collected through questionnaires distributed to 221 respondents who use or are familiar with e-wallet payment systems in Makassar City. Hypothesis testing was conducted using bootstrapping techniques through t-statistics and p-values. The findings reveal that perceived usefulness and trust significantly influence user intention, while perceived ease of use does not significantly affect adoption intention. In addition, user intention significantly affects user satisfaction. These findings contribute theoretically by extending TAM in the context of digital payment adoption and highlighting trust as a critical factor in emerging financial technology environments. Practically, the study provides insights for fintech developers and policymakers to strengthen system functionality, security, and user trust in order to encourage sustainable adoption of digital payment systems.